Implementasi Nilai Dasar ASN BerAKHLAK Berbasis Penilaian Teman Sejawat Terintegrasi Reward And Punishment di SMK Negeri 1 Koto Besar - Andison Andison (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2023)
The improvement of the quality of educational unit organizers is carried out through an organizational culture implemented by the head of the educational unit. The head of the educational unit in this case plays a managerial and supervisory role in improving the quality of the educational organization. The implementation of quality improvement in this regard is carried out through the implementation of the basic values of civil servants (ASN) based on peer assessment, which is then integrated with rewards and punishments. This is done in accordance with the goals of the school action research, which aims to enhance the integrity and performance of the school organization. The School Action Research (PTS) in this case is carried out at SMK Negeri 1 Koto Besar with the research subjects being educators, educational personnel, as well as the head and deputy head of the educational unit. The School Action Research (PTS) is conducted in 2 cycles, and after data collection and analysis, the following conclusions are drawn: there is an increase in integrity in the school organization at SMK Negeri 1 Koto Besar through peer assessment in the implementation of the basic values of civil servants (ASN). The percentage ranges from 12% for discipline to below 5% for the indicators of professionalism, cooperation, loyalty, honesty, work initiative, commitment and responsibility, service orientation, and social personality, which need to be optimized as they have not yet met the requirements. As a form of appreciation and motivation, rewards in the form of certificates and material rewards, as well as punishments in the form of reduced teaching hours, have a positive impact on instilling the value of integrity in the educational unit.